Transbronchial drainage using endobronchial ultrasonography with guide sheath for lung abscess: A case report. Issue 20 (May 2018) - Yaguchi, Daizo; Ichikawa, Motoshi; Inoue, Noriko; Kobayashi, Daisuke; Shizu, Masato; Imai, Naoyuki
Abstract: Rationale: Lung abscess was previously treated surgically, but is now mainly treated with antibiotics and ideally with direct drainage, although postural drainage canalso be used. Patient concerns: A chest abnormal shadow was detected in an 82-year-old man and he was referred to our department in November 2017. On chest computed tomography (CT), a low-density mass shadow was present in the left S8 segment. Lung abscess and lung cancer were considered as differential diagnoses, and treatment with sulbactam sodium/ampicillin sodium (SBT/ABPC) was first initiated for lung abscess. The etiologic agent could not be identified by sputum examination, and the abscess shadow remained. Diagnoses: Lung abscess. Interventions: Endobronchial ultrasonography with a guide sheath (EBUS-GS)-guided bronchoscopy was performed on hospital day 21 to diagnose the lesion, identify the etiologic agent if the lesion was a lung abscess, and attempt drainage. Vacuum aspiration performed in the guide sheath after the probe was placed within the lesion produced 4-5 ml of gray turbid pus, and the abscess was judged to have been drained. Outcomes: A subsequent pathological examination did not detect malignant cells. Klebsiella pneumoniae, Prevotella spp. was identified as the etiologic agent in bacteriological tests. Antibiotics were changed based on sensitivity test results, and drainage was similarly performed on hospital day 28. The shadow gradually improved and disappeared. Therefore, this procedure and treatment led to identification of the etiologic agent and helped with cure of the disease. Lessons: Based on the basic principle of treatment for abscess using as much drainage as possible, EBUS-GS-guided transbronchial drainage may be considered to be a "new procedure" for lung abscess.